Evaluating the eighth edition TNM staging system for esophageal cancer among patients receiving neoadjuvant therapy: A SEER study - Yonggang Yuan; Ge Ma; Xuelei Hu; Qingyuan Huang (Cancer Medicine)
Abstract Background The evaluation of the eighth edition of ypTNM staging system for patients with esophageal cancer was limited in the setting of neoadjuvant therapy. Methods A total of 2324 patients with esophageal cancer receiving radio(chemo)therapy prior to surgery from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2013 were eligible for the analysis. Kaplan‐Meier method and Cox proportional hazards models were used to estimate overall survivals. Results Among patients with preoperative therapy, both the seventh edition TNM grouping and the eighth edition ypTNM grouping could significantly stratify the overall survival (both log‐rank P < .001). There was not significant difference in the C‐index of the seventh edition TNM grouping (0.575; 95%CI, 0.558‐0.593) and the eighth edition ypTNM grouping (0.569; 95%CI, 0.551‐0.587) (P = .098). In multivariable Cox analysis, ypN category was the strongest predictor of overall survival (P < .001), followed by tumor grade (HR, 1.33; 95%CI, 1.12‐1.56; P = .001). The combination of ypT, ypN, and ypG categories yielded significantly higher C‐index (0.591; 95%CI, 0.573‐0.609) than that of the seventh edition TNM staging (P = .024). Conclusion Tumor grade remained an independent predictor of overall survival in the setting of neoadjuvant therapy, and could improve the performance of ypTNM staging system.